Hukum Bukanlah Idealisasi Moral Masyarakat - Suparman Marzuki (Unisia, 2003)
The incompatibility of Indonesian legal system with the effort for creation of Justice and economic welfare, closely links to the conceptual ground and integralistic state framework which strongly leads to give more power for the state, and not for the society. The solution needed is to push the law to further move from repressive law system toward autonomous law or responsive law.